"What Should I Be When I Grow Up?" Vocational Discernment and Spiritual Well-Being. Issue 1 (2nd January 2018) - Dunlap, Garland T.
Abstract: The purpose of this article is to describe a systematic method of evoking students' vocational discernment through the practice of spiritual well-being. Engaging spiritual well-being as a means of vocational discernment requires that the student and the advisor explore the student's sense of connectedness by tapping into the tacit dimension of spirituality and to make the tacit explicit. Vocational discernment is a conceptual activity in which students examine their individual design, community affirmation, and transcendent beliefs to help point to and highlight their sense of place.